Las sentencias dictadas por los jueces no especializados en materia constitucional - Del Pozo Larrea, Susan Fernanda (2018)
In the development of this research, we have analyzed the judgments of first level judges not specialized in constitutional matters regarding the jurisdictional guarantees established in the Constitution of the Republic of Ecuador and regulated by the Organic Law of Jurisdictional Guarantees and Constitutional Control. At present, the judges have the investiture of constitutional justice administrators, however, not all apply the procedure that should be given to such important legal precepts as unrestricted right of all citizens, generating the violation of constitutional and legal rule in the emission of its failures. The objective of this titling work is to determine whether the judgments issued by the first level jurisdictional entity comply with the provisions of our constitutional and legal norm, which is why a description of the jurisdictional guarantees that are the competence of judges of first level, as well as a legal and critical analysis of the content of the sentence in constitutional matter, also describing the role of the judge a quo and finally analyzing two sentences of jurisdictional guarantees issued by that authority. The methods applied were inductive, historical-logical, analytical, descriptive and exegetical. The obtained results have allowed to generate a contribution to the university community and law professionals who show interest in the proposed subject so that they can use this titling work as a source of consultation and support in their technical defenses.